AMERİKAN FELSEFESİNİN YENİDEN CANLANIŞI: JOHN J. MCDERMOTT - Celal Türer (Felsefe Dünyası)
John McDermott has played a primary role in the great renascence of interest in the history of American philosophical thought since 1958 and he has contributed and continues to contribute to advancement of that tradition in numerous areas. McDermott's work on the history of American philosophy has focused upon the 'classical' period but he does not limit himself to these years or figures. McDermott believes that there is something extraordinary about the classic period. He belives that experience is our only teacher. He wants to develop an "aesthetic sensibility" revealing "how we and others feel our situation and feel about our situation. According to McDermott American philosophy/experiences may be able to offer something to the next centry, by serving as a model. So he attempts to utilise the insights of that tradition in an effort to confront the significant problems of our time. In his interpreting of American philosophy he focused on not only story of ideas but also of people since he believes that these stories are dramatic centers of life and represent pragmatic core of American culture.